First genotype-phenotype study reveals HLA-DQβ1 insertion heterogeneity in high-resolution manometry achalasia subtypes. Issue 1 (February 2019) - Vackova, Zuzana; Niebisch, Stefan; Triantafyllou, Tania; Becker, Jessica; Hess, Timo; Kreuser, Nicole; Kanoni, Stavroula; Deloukas, Panos; Schüller, Vitalia; Heinrichs, Sophie KM; Thieme, René; Nöthen, Markus M; et al.
Background: Achalasia is a primary oesophageal motility disorder. Although aetiology remains mainly unknown, a genetic risk variant, rs28688207 in HLA-DQB1, showed strong achalasia association suggesting involvement of immune-mediated processes in the pathogenesis. High-resolution manometry recognises three types of achalasia. The aim of our study was to perform the first genotype-phenotype analysis investigating the frequency of rs28688207 across the high-resolution manometry subtypes. Methods: This was a cross-sectional retrospective study. Achalasia patients from tertiary centres in the Czech Republic ( n = 163), Germany ( n = 114), Greece ( n = 70) and controls were enrolled. All subjects were genotyped for the rs28688207 insertion. The Kruskal–Wallis test was used for the genotype-phenotype analysis. Results: A total of 347 achalasia patients (type I – 89, II – 210, III – 48) were included. The overall frequency of the rs28688207 was 10.3%. The distribution of the insertion was significantly different across the high-resolution manometry subtypes ( p = 0.038), being most prevalent in type I (14.6%), followed by type II (9.5%) and III (6.3%). Conclusion: The frequency of the HLA-DQB1 insertion differs among high-resolution manometry achalasia subtypes. The insertion is most prevalent in type I, suggesting that immune-mediated mechanisms triggered by the insertion may play a more prominent role in the pathogenesis of this subtype.